2019
DOI: 10.1002/mgg3.929
|View full text |Cite
|
Sign up to set email alerts
|

AMBN mutations causing hypoplastic amelogenesis imperfecta and Ambn knockout‐NLS‐lacZ knockin mice exhibiting failed amelogenesis and Ambn tissue‐specificity

Abstract: Background Ameloblastin (AMBN) is a secreted matrix protein that is critical for the formation of dental enamel and is enamel‐specific with respect to its essential functions. Biallelic AMBN defects cause non‐syndromic autosomal recessive amelogenesis imperfecta. Homozygous Ambn mutant mice expressing an internally truncated AMBN protein deposit only a soft mineral crust on the surface of dentin. Methods We characterized a family with hypoplastic amelogenesis imperfecta caused by AMBN compound heterozygous mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 63 publications
1
14
1
Order By: Relevance
“…In addition, the enamel layer achieves its full thickness and normal contour by Level 3 in all three genotypes. This is very different from the bSEM results when a gene necessary for the secretory stage is affected and the enamel layer fails to expand significantly, as in amelogenin 34 , 35 , enamelin 36 , ameloblastin 37 , and matrix metallopeptidase 20 (MMP20) 28 , 38 null mice.
Figure 6 bSEM of 7-wk Odaph +/+ , Odaph +/C41* , and Odaph C41*/C41* Mouse Mandibular Incisor Cross-Sections.
…”
Section: Resultscontrasting
confidence: 62%
“…In addition, the enamel layer achieves its full thickness and normal contour by Level 3 in all three genotypes. This is very different from the bSEM results when a gene necessary for the secretory stage is affected and the enamel layer fails to expand significantly, as in amelogenin 34 , 35 , enamelin 36 , ameloblastin 37 , and matrix metallopeptidase 20 (MMP20) 28 , 38 null mice.
Figure 6 bSEM of 7-wk Odaph +/+ , Odaph +/C41* , and Odaph C41*/C41* Mouse Mandibular Incisor Cross-Sections.
…”
Section: Resultscontrasting
confidence: 62%
“…On the other hand, an increased amount of both intracellular and extracellular AMEL found in the mutant incisor might impede elongation and proper orientation of mineral ribbons. Interestingly, the numerous ectopic mineral depositions in the Acp4 mutant incisors and molars appear similar to those found in the Enam and Ambn null mice, although to a lesser extent 45 , 68 , 69 . Along with the finding that ACP4 localizes to the Tomes’ process, the above observations suggest that ACP4 is essential for both initiation and elongation of enamel mineral ribbons probably through regulating secretion or turnover of EMPs around mineralization front apparatus 69 , 70 .…”
Section: Discussionsupporting
confidence: 67%
“…It is also conceivable, however, that AMEL arose in sarcopterygians and SCPP5 in actinopterygians. Studies of gene-disrupted mice showed that both AMBN and ENAM are necessary for enamel ribbon formation, the unique mineralization process of enamel, whereas AMEL is not ( Smith et al., 2016 ; Liang et al., 2019 ). Furthermore, a thin enamel can form in AMEL -deficient mice and in toothed whales that have deleterious mutations in AMEL , if both AMBN and ENAM are functional ( Gibson et al., 2001 ; Kawasaki et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%